Youth At-Risk in High Schools. Tracking, Exclusion and Inequality: ‘Hearing Their Voice" - Israel, Lili (My University, 2021)
The research uses the qualitative paradigm, which presents reality as the respondents’ subjective perception. The research examines the topic of tracking and the contexts in the research participants’ reality of school life, with reference to the twelve years of their studies.The research method is ethnographic. The research seeks to understand and explain the phenomenon of tracking and what is derived from it in the students’ scholastic life and as it occurs. The researcher has perceptions that constitute a conceptual network that contributes to the empirical outlook. The ideological approach in ethnography is the desire to understand the other from unmediated closeness, listening, and observation, entry into the field, creation of a relationship with people, choice of the categories, in-depth conversations, and mapping of the relationships. Ethnography helps to understand what influences the social structures in the aspects of policy, economy, culture, and education as well as structures that preserve or create social inequality. This research approach enabled the researcher to interpret and decode social situations on the topic of tracking and exclusion. Ethnographic research addresses the contexts created in the encounter between the researcher and the research respondents in the researched field. The interviewees’ experiences, the language, the voice, their expressions and explanations and examples about the phenomena are the tool of analysis according to the theoretical system of concepts.

Praca dotyczy zagadnień zagrożonej młodzieży izraelskich szkół średnich. W szczególności podjęto tytułowe zagadnienia edukacyjnego ścieżkowania, wykluczenia oraz nierówności społecznych, w tym nierówności edukacyjnych.Badania zrealizowano wykorzystując jakościową strategię gromadzenia informacji. Głównym ich celem było ukazanie procesu ścieżkowania oraz szkolnego kontekstu, w którym on przebiega, ze szczególnym uwzględnieniem biografii uczniowskich rekonstruowanych w odniesieniu do dwunastu lat kształcenia.Badanie wykorzystuje elementy metody etnograficznej, tj. odnoszą się do konkretnej, szkolnej rzeczywistości danego czasu i miejsca. Ich celem jest eksploracja zjawiska ścieżkowania, jego diagnoza oraz zrozumienie i wyjaśnienie jego uwarunkowań.Podjęte w pracy postępowanie badawcze umożliwiło autorce interpretację obserwowanych zjawisk i procesów związanych z wykluczeniem i ścieżkowaniem. Proces dekodowania wsparty był wieloletnim doświadczeniem autorki oraz tradycją badań etnograficznych w naukach społecznych i systematycznie adaptowany na pedagogiczny grunt rozważań o współczesnej szkole.
Młodzież zagrożona w szkołach średnich. Ścieżkowanie, wykluczenie oraz nierówność: „Słysząc ich głos”
Wydział Studiów Edukacyjnych
Keywords: youth; educational tracking; exclusion; social inequalities; młodzież; ścieżkowanie w edukacji; wykluczenie; nierówności społeczne